Rys historyczny Teatru Muzycznego Takarazuka – w poszukiwaniu nowego „teatru narodowego” - Lecińska-Ruchniewicz, Monika (Slavia Occidentalis, 2017)
The Takarazuka Revue (Takarazuka Kagekidan) occupies an important place among Japanese modern theatres and enjoys unwavering popularity both in Japan and abroad. Both the artistic and commercial character of the idea that brought the first Japanese all-female revue to life in 1914 determined its further development and process of conversion from a simple choir to a full scale musical theater. Kobayashi – the founder of the Takarazuka Revue, an opera aficionado and theater critic – was driven by the need to create a new, affordable and easily understandable national theater that would meet the needs of modern Japanese society. Currently, the Takarazuka Revue is one of the most active and successful modern Japanese theaters. Its harmonious combination of trends in mass culture and Japanese and Western theatrical traditions is fascinating. The highly characteristic fusion of simplicity and splendour, kitsch and sophistication that can be seen in the revue’s works, creates a unique, albeit somewhat controversial style, complemented by musumeyaku (female emploi) i otokoyaku (male emploi) played by actresses taught in a special school affiliated to the Takarazuka Revue.